2009
DOI: 10.1002/ejoc.200900168
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Characterization of the Most Stable, Highly Symmetric Isomer of C60(CF3)18

Abstract: The high thermal and chemical stability of C3v‐C60(CF3)18 allowed its isolation from a complex C60(CF3)n isomer mixture followed by characterization with 19F NMR spectroscopy and single‐crystal X‐ray crystallography. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“… 54 The isomer with this addition pattern, 60-18-2 , has been isolated and characterized by single-crystal X-ray diffraction. 82 It is followed by four isomers with SPP moieties (Δ E = 9–28 kJ·mol −1 ). Note that these isomers span a larger range of relative energies than TMFs with 8, 10, 14, and 16 CF 3 groups.…”
Section: Pfaf Addition Patternsmentioning
confidence: 99%
“… 54 The isomer with this addition pattern, 60-18-2 , has been isolated and characterized by single-crystal X-ray diffraction. 82 It is followed by four isomers with SPP moieties (Δ E = 9–28 kJ·mol −1 ). Note that these isomers span a larger range of relative energies than TMFs with 8, 10, 14, and 16 CF 3 groups.…”
Section: Pfaf Addition Patternsmentioning
confidence: 99%
“…71 Synthesis, partial isolation and X-ray structure determination of C 3v -C 60 (CF 3 ) 18 , the most stable and symmetric isomer of this composition, have been reported. 72 DFT was used to analyse the evolution of the structure and electronic properties of the fullerene derivatives C 60 (CF 3 ) n (n = 2, 4, 6, 10). It was found that the C 60 (CF 3 ) 6 is the most stable structure.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
“…Because of the higher steric demand of bulkier CF 3 groups, the C 94 (CF 3 ) 20 molecule can be regarded as overcrowded. For comparison, all other structurally characterized CF 3 derivatives of fullerenes (C 60 ,13 C 70 ,14 C 86 7c), or C 88 9) contain at most 18 attached groups. It should be noted that the average C‐C‐CF 3 angle at THJ positions (109.8°) is significantly smaller than at PHH junctions (112.5°) owing to the difference in cage curvature.…”
mentioning
confidence: 99%